Economic analysis of urban water resources under drought: understanding water management and planning in South Africa - Aina, Ifedotun (School of Economics, 2024)
Water scarcity is of the utmost importance for sustaining life and human development. This growing challenge is expected to worsen because of the changing dynamics observed in many countries worldwide. The increasing demand for water, driven primarily by population growth, is one of the main factors contributing to water scarcity. As the world's population continues to grow, so does demand for water for domestic purposes. Climate change is another significant factor exacerbating water scarcity. Changing weather patterns, such as reduced rainfall and the increased frequency and severity of droughts, affect water availability, making it more challenging to meet the growing demand for water. Economic progress is also a significant factor that contributes to water scarcity. Economic development often translates to increased water usage for economic production purposes, leading to overexploitation of water resources. Consequently, many countries face water shortages, which have adverse consequences for the environment and economy. Given these changing dynamics, it is crucial to reconsider the management and allocation of water resources. Therefore, it is important to develop sustainable water management policies that balance the competing demands for water and protect the environment and economic growth. This thesis contributes to the field of water resource management by leveraging insights from economic and environmental modelling methods. This thesis presents three papers with the common goal of understanding specific themes in the water sector, namely, households' preferences for water conservation technologies, the impact of tariffs on the choice of water supply source, and policy measures to optimize water allocation decisions in large water systems. It focuses on the case of South Africa and examines the challenges of water scarcity and management, providing a comprehensive understanding of the factors driving it and possible solutions to mitigate its impacts. The focus on South Africa is important because of its economic position in sub-Saharan Africa and its complex and diverse sets of water management challenges. Moreover, similar to many arid and semi-arid regions, the country faces extreme water scarcity and a high water demand for domestic and economic purposes. Hence, this study is likely to provide insights into enhancing water management initiatives in many other water-stressed countries. The first paper on household preferences for water saving technologies contributes to the discussion on climate change adaptation strategies in urban areas. This study aimed to investigate heterogeneity among households based on their preferences for the characteristics of four different water-saving technologies. This is achieved by analyzing the attributes that would drive the installation and adoption of water-saving technologies by urban dwellers in Cape Town. Using a choice modeling framework, primary survey data were gathered from 512 urban households located in five major suburbs of the city. Four preference classes were identified to account for taste heterogeneity. The results showed that members of Classes 1 and 2 expressed a high interest in technologies that could save a significant amount of water, whereas respondents in Classes 3 and 4 preferred inexpensive conservation and behavioral habits as climate adaptation measures. These findings have significant policy implications for water-stressed and arid cities, both within and outside South Africa, as many large cities require long-term measures to alleviate the pressure on their water systems, similar to Cape Town. The second study contributes to the literature on public utility regulation. This study estimates a household water demand system and investigates the substitution threshold of piped water and self-supplied groundwater sources for the better planning of water supply systems. Using a pooled cross-sectional dataset from the South African General Household Survey (GHS), the analysis showed a high substitution threshold for piped water and self-supplied groundwater. The results also provide insights into the potential welfare impact of a stylized piped water tariff change that leads to increased piped water choices in the study area. Finally, the third study presents the development of an integrated hydroeconomic model for a large water system in which the urban and agricultural sectors are the dominant water users, and climate change presents a major environmental challenge. This study uses data from the Western Cape Water Supply System (WCWSS) and analyzes the effects of two water allocation policies: water markets and proportional sharing. The results show the enhancement of the economic benefits that can be achieved when high-value water users are prioritized. This study proposes strategies for water resource management, given the imminent impacts of climate change on water availability in the coming decades.